KOMPOSISI MINYAK ATSIRI DARI TIGA JENIS TUMBUHAN RUTACEAE [ Composition of Essential Oils from Three Rutaceae Species Plant] - Agusta, Andria; Jamal, Yuliasri (BERITA BIOLOGI, 1999)
Rutaceae is one of the essential oil resources that is very potential for medicinal, perfumery and other use This study was conducted to analyze the essential oil components resulted from water distillation of kalamanjarik leaves (Micromelum minutum), jeruk epara leaves ILimnocitrus litoralis) and the leaves and the stem bark of malapotung (Evodia qlabra). The results showed the leaves of kalamanjarik contained approximately 0,70%, jeruk jepara 0,21%, malapotung leaves 0,17% and the stem bark contained 0,50 % essential oils. GCMS analyses of the essential oils gave 3 major components of kalamanjarik leaves i.e /J-pinene (24,41%j, bergamiol (23,01%) and nerolidol (18,90%) and 2 major components of jeruk jepara leaves i.e fl-mircene (70.55) and /t-pinene (24,06 %). Essential oil of malapotung leaves consisted of 39,8J% ct-pinene, 14,26 % 1aR(1aa,4a/3,7a,7aa,7ba)decahydro -1,1,7-lrimethyl-4-methylene-1H-cycloprope azulene and 16,62% S-cadinene as major components, while the stem bark had only one major component, u-pinene (68,37 %) The minor components of the four essential oils will be discussed.